2021
DOI: 10.52634/mier/2017/v7/i2/1422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Facebook Addiction Disorder (Fad) on Study Habits and Academic Achievement of Adolescents

Abstract: With the present era being technology driven, social media has become an indispensable part of many people irrespective of their age. Among different age groups, the maximum users are adolescents and among different social networking sites (SNS), Facebook shares the major part of usage by them. Many adolescents are tending towards excessive usage of Facebook leading to its addiction. Does this addiction have negative influence on adolescents or it actually helps them to keep up with their counterparts and be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…The study found that Facebook addiction has negative relationship with academic performance of the students, as indicated by the last semester's GPA report [β: -10.01, 95% CI: -10.85,- (-9.18)]. This finding is in agreement with the previous studies conducted in India [11], Iraq [9], Pakistan [35], and Sri Lanka [10]. Although various studies have found that Facebook addiction has negative effects on university students, a study from Pakistan [4] found that Facebook could help with communication and information gathering.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The study found that Facebook addiction has negative relationship with academic performance of the students, as indicated by the last semester's GPA report [β: -10.01, 95% CI: -10.85,- (-9.18)]. This finding is in agreement with the previous studies conducted in India [11], Iraq [9], Pakistan [35], and Sri Lanka [10]. Although various studies have found that Facebook addiction has negative effects on university students, a study from Pakistan [4] found that Facebook could help with communication and information gathering.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is supported by a prior study [ 31 ], in which up to 20% of Facebook-addicted students reported anxiety and depressive symptoms. Similarly, the study conducted among Pakistani students [ 11 ] revealed a strong positive relationship between Facebook addiction and the symptoms of anxiety and depression. Furthermore, we identified a number of previous studies [ 32 , 39 – 42 ] that reported the negative correlation of Facebook addiction with anxiety and depressive symptoms in university students.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a bid to escape from the harsh realities of university life, students may develop a recurring habit of use that is excessive and addictive. Vashishta, Ahuja, and Sharma (2017) saw this addiction as a disorder with telling repercussion on learners.…”
Section: Introduction/literature Reviewmentioning
confidence: 99%